The Effect of Balance Training on the Risk of Falls in the Elderly in Mongolato Village, Telaga District - Radhiannisa Permata Bakri; Rona Febriyona; Inne Ariane Gobel; Gladys Maristela Rawung (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
In the elderly, there is regression and morphological changes in muscles and bones, so that the elderly are at high risk of falling. Methods that can be applied to prevent the impact of falls are physical exercises, one of which is balance exercises with tandem exercises. This study aims to find out how the Effect of Balance Training on the Risk of Falls in the Elderly in Mongolato Village, Telaga District. The quantitative method with the research design used in this study is pre-experiment, one group pre-post test design, where the sample was selected through the purposive sampling method, with a sample of 39 elderly respondents in Mongolato Village. The results of the study showed that there was an effect of Balance Training on the Risk of Falls in the Elderly in Mongolato Village, Telaga District with a p. value of 0.000 < 0.05. Balance exercises are very important in preventing and as a treatment to reduce the risk of falls in the elderly.